Characterizing dryland crop-based livelihoods: Insights from surveys in Kenya and Uganda - Narmandakh, Davaatseren; Kirui, Leonard; Marenya, Paswel; Chipindu, Lovemore; Bett, Charles; Opie, Hellen (International Maize and Wheat Improvement Center, 2024)
This report examines food security and farming systems among sorghum and millet cultivators in Kenya and Uganda, based on a survey of 2,701 households conducted in May–June 2023. The study reveals high rates of food insecurity (measured as food poverty) among these farmers, 53.2% in Kenya and 78.1% in Uganda, exceeding national averages. Cereals provide the majority of calories and dietary diversity is limited, with about half of the households surveyed consuming fewer than five food groups daily. The analysis shows that sorghum and millet farming is characterized by low use of inputs, limited market participation, and significant production challenges from drought, pests, and diseases. Farmers operate with minimal farm expenditures (US $23.20–81.00 in Kenya and $12.40–15.07 in Uganda annually), and adoption of improved varieties remains low except in Eastern Kenya. Using decision tree analysis, the study identifies key determinants of food insecurity, including household size, education levels, land holdings, and crop diversification. The findings suggest that targeted interventions that take into consideration farming system characteristics, market access, and household demographics are crucial for improving food security among dryland cereal farmers in East Africa